Impact investing: portfolio company selection in Latin America - Oppenheimer, Fabian (2014)
The paper analyses how Impact Investors select their portfolio companies in Latin America and what criteria are assessed in the process. Since virtually no research on this has been conducted to date, and since the selection process model applied in Venture Capital is not dissimilar, that approach has been adopted. The findings reveal that Impact Investors originate and assess deals in a similar way to Venture Capitalists, but that some criteria are adjusted and others added in order to reflect the dual objective of Impact Investing. Impact Investors can originate deals passively, but they prefer searching for social ventures proactively: personal contacts, access to networks and industry events are crucial in this context. Impact Investors considering an investment in Latin America search for integer, honest and reliable social entrepreneurs committed to social impact; eligible social ventures must be profitable with potential for further scalability; the product must have a social impact, i.e. create value for the individual consumer and for the wider community; market size and market growth are crucial external factors; and the deal features depend on the investor’s risk attitude and the prospects of a successful exit in both financial and social terms. Impact Investors are also willing to provide non-financial support prior to an investment, if a social venture shows high potential for achieving their dual objective.